2008
DOI: 10.1248/cpb.56.1213
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metal-Catalyzed Asymmetric Reactions Using P-Chirogenic Diaminophosphine Oxides: DIAPHOXs

Abstract: This review describes the development of a new class of chiral phosphorus ligands: amino acid-derived Pchirogenic diaminophosphine oxides, DIAPHOXs, and their application to several transition metal-catalyzed asymmetric allylic substitution reactions. Pd-catalyzed asymmetric allylic alkylation with cyclic b b-keto esters as prochiral nucleophiles was initially examined using P-chirogenic diaminophosphine oxide 1a, resulting in highly enantioselective construction of quaternary stereocenters. Mechanistic invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 165 publications
0
9
0
Order By: Relevance
“…An elegant synthesis of a HASPO with an stereogenic phosphorus atom was reported by Hamada and co-workers (Scheme 11). 10,[43][44][45] In this methodology, L-aspartic acid was converted in a few steps into a chiral triamine. A diastereoselective formation of the corresponding triaminophosphine using PCl3, followed by the subsequent hydrolysis yielded the desired diaminophosphine oxide (DIAPHOX).…”
Section: Non-racemic Sposmentioning
confidence: 99%
“…An elegant synthesis of a HASPO with an stereogenic phosphorus atom was reported by Hamada and co-workers (Scheme 11). 10,[43][44][45] In this methodology, L-aspartic acid was converted in a few steps into a chiral triamine. A diastereoselective formation of the corresponding triaminophosphine using PCl3, followed by the subsequent hydrolysis yielded the desired diaminophosphine oxide (DIAPHOX).…”
Section: Non-racemic Sposmentioning
confidence: 99%
“…The principal investigation was performed with symmetric secondary substituted compound 16 and the addition of 4 equiv BSA to toluene‐D 8 . The experiment was controlled at different times; however, the best result was obtained after 24 h. The reaction was much slower compared to five‐membered ring diaminophosphine oxides like DIAPHOX 5 . The 31 P NMR showed that pentavalent ligand 16 (chemical shift: 8.1 ppm, toluene‐D 8 ) reacted with BSA to provide the formation of a trivalent phosphorus species (chemical shift: 117.4 ppm, toluene‐D 8 ) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…15 , 1H, H-1 ), 3.78 -3.74 (m, 2H, H-1 , H-3 21 (m, 2H, H-4), 1.81 -1.72 (m, 2H, H-5), 1.38 (s, 3H, H-8), 1.14 (s, 3H, H-6), 1.05 (s, 3H, H-7) ppm. 13 (14). Prepared from monoarylated diamine (0.30 g, 1.02 mmol), triethylamine (0.17 mL, 1.22 mmol) and 2,4,6-trimethylbenzyl chloride (0.19 g, 1.12 mmol) in acetonitrile (10 mL).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…[112] Pioneering work came from Nemoto, who reviewed recently the main aspects of diaminophosphine oxides (DIAPHOX, Figure 8) in transition metal-catalyzed asymmetric reactions. [113] The groups of Pugin and Pfaltz synthesized mixed secondary phosphine oxides/phosphines called JoSPOphos, owing to their similarity to the well established family of JosiPhos ligands (Schemes 45 and 54). [114] In the first step Ugi-amine was brominated.…”
Section: Preligands and Self-assembling Catalystsmentioning
confidence: 99%